Evaluasi Elemen Merek Mal SKA Pekanbaru Dalam Upaya Mempertahankan Eksistensi - Dewi Martina; Johan Faladhin (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2019)
This research describe about how SKA Mal as one of the biggest shopping centre in Pekanbaru could maintain their existence for 15 years, since 2004. The ability of SKA Mal who was a local mal and should compete with a new big mal with a national scale. This new mal come in 2018, named Living World Pekanbaru. The presence of Living World from national scale was a new alternative option for Pekanbaru citizen to shop or refreshing. Also, this Living World Pekanbaru is the second Living World after the one in Banten near to Jakarta. Another threat for SKA Mal is the presence of Transmart in 2017. Although this one is not that a big threat for SKA Mal because the type of shopping centre is a little bit different. The ability of a brand to keep on running is with maintaining their existence. It’s is seen from how that brand see the power of each brand element. They are name of brand, logo and symbol, character, package, slogan and jingle. Evaluation for each brand element could seen from the character of each element as what Keller said (2006). The discussion will use the qualitative method with collecting the qualitative data and explained with descriptive analiysis to the evaluation of brand of SKA mal in order to confront the competition and market develop of Pekanbaru city.